Functional analysis of the SUMOylation pathway in Drosophila. - Talamillo, A.; Sánchez, J.; Barrio, R. (Biochemical Society Transactions, 2008)
SUMOylation, a reversible process used as a 'fine-tuning' mechanism to regulate the role of multiple proteins, is conserved throughout evolution. This post-translational modification affects several cellular processes by the modulation of subcellular localization, activity or stability of a variety of substrates. A growing number of proteins have been identified as targets for SUMOylation, although, for many of them, the role of SUMO conjugation on their function is unknown. The use of model systems might facilitate the study of SUMOylation implications in vivo. In the present paper, we have compiled what is known about SUMOylation in Drosophila melanogaster, where the use of genetics provides new insights on SUMOylation's biological roles.